A short book of public health - Muthu, V.K (Jaypee Brothers Medical Publishers (P) Ltd, 2014)
This book is an attempt to bring out a smaller volume on public health especially to cater to the needs of students and public health personnel like sanitary inspectors, nurses and doctors. The language of the text is easy to understand and enhances the clarity of the principles and concepts. The contents have been organized into 9 chapters. The initial chapters discuss strategies for providing health care, concepts in preventing diseases, epidemiology of communicable diseases, non-communicable diseases. Includes demography, family planning and maternal, child health, nutrition, school health service and principles of health education. The last chapters deal with health systems and health care programmes, basic statistics in health care, disinfection procedures, vector control methods, immunization schedule, etc